A Patented Rapid Method for Identification of Italian Diatom Species - Camilla Puccinelli (International Journal of Environmental Research and Public Health, 2019)
The study of diatoms—unicellular algae of the class Bacillariophyceae—has several applications, first and foremost the evaluation of freshwater ecosystem quality according to the Water Frame Directive 2000/60/EC (WFD). Identification at the species level is a crucial step in diatom studies, considering that species belonging to the same genus have different geographical distributions and different ecological requirements. The Rapid Method for Identification of Italian Diatom Species is aimed at guiding users in the classification of freshwater diatom species. It consists of a digitized flow chart that leads, step by step, to the identification, starting with an image capture by light or electron microscopy. This rapid and easy tool could be useful to workers of an environmental agency when performing the operational monitoring required by the WFD to classify surface waters. It will also expand the application of diatoms in numerous fields. This method has been patented in Italy.